Armerika - Richistan - Jacobi, Otto (2012)
Abstract: Sammelbesprechung: (1) Jacob S. Hacker & Paul Pierson (2010): Winner-Take-All Politics. New York: Simon & Schuster. (2) Paul Krugman (2007): The Conscience of a Liberal. New York: Norton & Company. (3) Paul Krugman (2012): End This Depression Now! New York: Norton & Company. (4) Paul Krugman (2012): Vergesst die Krise! Frankfurt: Campus Verlag. (5) Joseph E. Stiglitz (2010): Freefall - America, Free Markets, and the Sinking of the World Economy. New York: Norton & Company. (6) Joseph E. Stiglitz (2011): Im freien Fall. München: Pantheon. (7) Joel Berg (2011): All You Can Eat - How Hungry is America? New York: Seven Stories Press. (8) Nelson Lichtenstein (2009): The Retail Revolution - How Wal-Mart Created a Brave New World of Business. New York: Metropolitan Books Henry Holt and Company